2010
DOI: 10.1073/pnas.0914295107
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-secreted hepatocyte growth factor plays a functional role in esophageal squamous cell carcinoma invasion

Abstract: Squamous cell cancers comprise the most common type of human epithelial cancers. One subtype, esophageal squamous cell carcinoma (ESCC), is an aggressive cancer with poor prognosis due to late diagnosis and metastasis. Factors derived from the extracellular matrix (ECM) create an environment conducive to tumor growth and invasion. Specialized cancer-associated fibroblasts (CAFs) in the ECM influence tumorigenesis. We have shown previously that the nature and activation state of fibroblasts are critical in modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(153 citation statements)
references
References 34 publications
7
146
0
Order By: Relevance
“…A recent experimental study indicated that mutant p53 and EGFR expression potentiated HGF/MET signaling (35). The present and previous results suggest that co-expression of MET and EGFR may play a key role in mesenchymal sarcomatous metaplasia of squamous cell carcinoma through mechanisms such as EMT in other type of carcinomas, with subsequent tumor progression.…”
Section: Discussionsupporting
confidence: 66%
“…A recent experimental study indicated that mutant p53 and EGFR expression potentiated HGF/MET signaling (35). The present and previous results suggest that co-expression of MET and EGFR may play a key role in mesenchymal sarcomatous metaplasia of squamous cell carcinoma through mechanisms such as EMT in other type of carcinomas, with subsequent tumor progression.…”
Section: Discussionsupporting
confidence: 66%
“…The CAFs surrounding the tumor cells have been shown to be particularly important for regulating migration and invasion of tumor cells (23). HGF was identified as a fibroblast-derived factor which is capable of causing epithelial cell scattering and stimulating the migration and invasion of cancer cells (24)(25)(26). MET is overexpressed in a substantial portion of the NSCLC tumors, ranging from 26% to 51% (27), and has also been associated with advanced cancer stage and poor patient survival (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of HGF by stromal fibroblasts induces the transformed esophageal epithelial cells to invade extracellular matrix; however, other unidentified factors may also cooperate with HGF in this process, which further highlight the significance of this pathway in esophageal carcinoma invasion and progression [84].…”
Section: Wwwintechopencommentioning
confidence: 99%